Differences in Anthropometric Characteristics between Athletes of Different Orientation, Handball and Volleyball - Marina Vukotic; Georgi Georgijev (Journal of Anthropology of Sport and Physical Education)
The main goal of this research is to determine whether there are statistically significant differences in the level of anthropometric indicators among athletes of different sports directions (handball and volleyball players), that is, to determine the differences in the changes in the anthropometric indicators of athletes. The study was conducted on a sample of 50 subjects, a male gender divided into two subsample, 25 handball players and 25 volleyball players aged 13-15. In this study, 12 anthropometric variables were tested: body height, arm length, leg length, knee diameter, bicrystalline range, bichromium range, body mass, median volume of the thorax, circumference, upper abdomen, skin abdomen and skin set of lower legs. For all applied variables, the central and dispersion parameters as well as measures of asymmetry and flattening were calculated, and the distribution normality was verified by Kolmogorov-Smirnov test. T-test was applied to verify that the system of applied variables has statistically quantitative differences between groups. On the basis of the obtained results, it can be concluded that there are statistically significant differences in anthropometric indicators in athletes of different sports orientations. This research can be used by trainers who realize training programs with these and other athletes in order to achieve better results.